In Memory of Reza Banakar: 1959-2020 : Socio‐Legal Agency in Late Modernity – Reappreciating the Relationship Between Normativity and Sociology of Law - Guibentif, P. (In times of pandemics and populism: increasing inequalities? (ISA RCSL Virtual Meeting 2021), 2021)
The paper takes as a starting point an article of Reza Banakar published 1998, in which he compared sociology of law with feminist scholarship, arguing, firstly, that the success of feminist scholarship would be due to the fact that feminist scholars ‘share a common ideological objective that does not exist to the same extent and with the same intensity in sociology of law’, and, secondly, that, just like feminists, who ‘freed themselves from the limitations of the traditional and academically established disciplines’, sociology of law ‘must in the same fashion limit its dependency on both law and sociology’. - The discussion of these two arguments may offer an appropriate structure for a contribution to the debate about the relationship between sociology of law and normative debates. In a first part, a case for a possible ideological objective for the Sociology of Law will be put forward. In a second part, the relationship between Law and Sociology will be discussed, with a view to this objective, proposing one possible understanding of Banakar’s programme of ‘Merging Law and Sociology’.